2016
DOI: 10.1371/journal.pone.0167933
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Treatment on Physical Function in Older Patients Hospitalized for Heart Failure: A Randomized Clinical Trial

Abstract: BackgroundFrailty is a characteristic of older patients with heart failure, who undergo functional decline during hospitalization. At present, continuous intravenous infusion of diuretics is widely used for the treatment of hospitalized patients with heart failure. In this prospective, randomized, open-label controlled trial, we tested whether an early switch from continuous intravenous infusion therapy to oral treatment with diuretics prevents functional decline in patients hospitalized for heart failure.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…28,29 Second, medications to rapidly improve decongestion lead to early ambulation and ADL preservation. 16,30 Third, as our data demonstrated that the albumin level at admission was a predictor of all-cause death, nutritional support might be a key strategy (Table 4). Finally, other approaches, such as educational programs and guideline-based therapy to improve HF prognosis, could contribute to preservation of the ability to perform ADL.…”
Section: Discussionmentioning
confidence: 85%
“…28,29 Second, medications to rapidly improve decongestion lead to early ambulation and ADL preservation. 16,30 Third, as our data demonstrated that the albumin level at admission was a predictor of all-cause death, nutritional support might be a key strategy (Table 4). Finally, other approaches, such as educational programs and guideline-based therapy to improve HF prognosis, could contribute to preservation of the ability to perform ADL.…”
Section: Discussionmentioning
confidence: 85%
“…This design is consistent with the nature of the research question, which does not aim to evaluate the efficacy of an intervention. Of the remaining three studies, two were Validation/Agreement studies [27,30], and one was a Randomised Controlled Trial (RCT) [31].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A variety of monitoring devices and algorithms were used, with the ActivPAL (PAL Technologies, Glasgow, UK) being the most commonly used device in studies concerned with posture (5 uses), and the Stepwatch Activity Monitor (Modus health, Washington, US) used most frequently for step count (4 uses). The validity of the methods used was reported by most studies, except for the Mediwalk Pedometer (Terumo, Japan), used by Ueda [31]. The range and validity of outcome measures used is available in Online Resource 4.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ueda et al reported that an early switch from continuous intravenous infusion to oral medication significantly prevented the functional decline during hospitalization. 22 In our study, 82.8% of the patients started TLV therapy from the first day of hospitalization, and the duration of continuous intravenous infusion was significantly shorter in patients treated with TLV therapy.…”
Section: Bed Rest Periodmentioning
confidence: 49%